Influence of altitudinal variation on the physical and biochemical characteristics of apple (Malus demostica) - KUMAR, PUSHPENDRA; SETHI, SHRUTI; SHARMA, R R; SINGH, SURENDER; SAHA, SUPRADIP; SHARMA, V K; SHARMA, SHASHI KUMAR; VARGHESE, ELDHO (The Indian Journal of Agricultural Sciences, 2019)
This study was conducted to investigate the physical and biochemical attributes of three Indian apple (Malus demostica Borkh.) cultivars as affected by elevation and genotype. High performance liquid chromatography was used to analyse sugars, organic acids and phenolic composition. Fructose and glucose were the most dominant sugars irrespective of genotype and altitude, while malic acid was the dominant organic acid. Chlorogenic acid was the main phenolics and valeric acid the most abundant fatty acid in apples. The variation in the fruit weight amongst different apple genotypes was larger (133.40 to 186 g) than firmness (10.32 to 11.87 N). The genotype Golden Delicious grown at 1800 msl had the highest ascorbic acid (28.80 mg/100 g) and total antioxidant (9.98 Î¼mol Trolox/g) content among the genotypes and elevations studied. The total phenol content was positively correlated with the elevation ranging from 82.5 mg/100 g (1400 msl) to 231 mg/100 g (1800 msl). A significant genotype Ã— elevation interaction was found for sugars and organic acid content, minerals and physical attributes. This study confirms the role of elevation as effective factor on the physical and nutritional quality in apple fruits.